The Effectiveness of the Electrocoagulation Process in Reducing TDS Concentration in Brackish Water in Subang Regency - Afiatun, Evi; Yustiani, Yonik Meilawati; Pradiko, Hary; Rahayu, Giga Galuh; Suju, Anis Dwiantoro (Journal of Community Based Environmental Engineering and Management, 2025)
Brackish water is a water resource that has the potential to be used as raw water, but has limitations due to high levels of total dissolved solids (TDS) This study aims to analyze the effectiveness of the electrocoagulation method in reducing these pollutant parameters in brackish water samples from Subang Regency. The groundwater samples were taken in the area of the Diniyah Takmiliyah Awaliyah Islamic Madrasa School. The research was conducted using a prototype electrocoagulation device with a pair of aluminum plates, varying voltages (10, 12, 14, and 15 volts), varying flow rates (0.06 L/second and 0.08 L/second), and conditions with and without a plate settler in the sedimentation unit. The results showed that increasing the voltage significantly reduced TDS levels. The highest efficiency was achieved at 10 volts with a flow rate of 0.06 L/second, reducing TDS from 3,400 mg/L to 3,110 mg/L (8.5%). Meanwhile, the lowest efficiency was achieved at 12 volts with a flow rate of 0.08 L/second, at 2.1%. Overall, this study confirms that electrocoagulation can be an alternative brackish water treatment technology in coastal areas. Although the TDS reduction efficiency is still limited, this method can be further developed as part of an integrated system to support sustainable clean water availability.